2015
DOI: 10.4025/actascibiolsci.v37i4.28059
|View full text |Cite
|
Sign up to set email alerts
|

<b>Pollen spectrum of the honey of uruçu bee (<i>Melipona scutellaris</i> Latreille, 1811) (Hymenoptera: Apidae) in the North Coast of Bahia State

Abstract: ABSTRACT.Regional-level studies of floral resources used by social bees for honey production can contribute to the improvement of management strategies for bee pastures and colonies, by identifying the most visited flowers and thus characterizing the various geographical origins of honey. The objective of this study was to investigate, through pollen analysis, the types of pollen and nectar sources used by the uruçu bee (Melipona scutellaris L.) in the North Coast of Bahia. Honey samples were taken monthly fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…According to Dórea et al (2017), Solanaceae species are frequently found in urban areas, and are used as pollen sources by solitary and social bees. Pollen types Solanum and S. paniculatum have also been found in the pollen spectrum of Meliponini honey in recent studies, such as Barth et al (2013), Nascimento et al (2015), Souza et al (2015) as well as Matos and Santos (2017).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…According to Dórea et al (2017), Solanaceae species are frequently found in urban areas, and are used as pollen sources by solitary and social bees. Pollen types Solanum and S. paniculatum have also been found in the pollen spectrum of Meliponini honey in recent studies, such as Barth et al (2013), Nascimento et al (2015), Souza et al (2015) as well as Matos and Santos (2017).…”
Section: Discussionmentioning
confidence: 85%
“…The families Anacardiaceae, Arecaceae, Euphorbiaceae and Fabaceae were the most representative in our study. Other authors (Oliveira et al, 2009;Ferreira & Absy, 2015;Souza et al, 2015;Matos & Santos, 2017) have also reported that species of these plant groups are important for cultivation of stingless bees. Plant species of these families should receive more attention by beekeepers and researchers of stingless bees to identify and conserve species of these taxonomic groups, important suppliers of trophic resources for stingless bee.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed by Alves et al (2006) to identify M. mandacaia nectar sources in the state of Bahia- Brazil, Souza et al (2015) of M. scutellaris on the north coast of Bahia, Matos and Santos (2016) of M. scutellaris in an Atlantic Forest area in the state of Bahia, and of Melipona fasciculata in the state of Maranhão-Brazil, indicated that the greatest diversity of types was also for the Fabaceae family. Therefore, this family, besides being the main supplier of pollen throughout the year, is one of the main sources of nectar for the stingless bees.…”
Section: Discussionmentioning
confidence: 99%
“…A modelling study suggested that M. scutellaris has low probability to occur in the Curitiba region in the next century even with climate change (Giannini et al, 2012) but further monitoring or controlled experiments would be required for a proper evaluation of the potential of the species to stablished self-sustaining populations in the wild and become invasive in the region. As a generalist species (Souza et al, 2015;BBPID) with a considerably long flight ranges (Araújo et al, 2004), M. scutellaris has potential to invade warmer regions of the country. In fact, data from SpeciesLink (Fig.…”
Section: Non-native Bee Speciesmentioning
confidence: 99%